2019
DOI: 10.15170/mm.2019.53.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Theatre Marketing – Analysis of Customers’ Satisfaction

Abstract: The aim of this paper was to identify key elements that create satisfaction of classic theatre audiences with respect to age (young (<35) vs. senior (35+) and theatre visiting frequency. It was measured as discrepancies between the level of theatre attendants' expectations from certain dimensions of theatre service and their experience evaluation with the same. METHODOLOGYThe research was conducted on a convenient sample using an in-person method in two different intervals: in the first interval research was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…Annak érdekében, hogy a jövőben is legyen zeneszerető közönségbázis, nagy figyelmet kell fordítani a fiatalabbak megszólítására és a "célpiac" kibővítésére, azaz új közönségrétegek elérésére. A fogyasztói elégedettség növelése, illetve új fogyasztók megszólítása kapcsán alapvető fontosságú az előadások célközönségének, az egyes fogyasztói szegmensek speciális igényeinek, elvárásai nak, érdeklődési körének megismerése, hiszen így válik lehetővé a kulturális tevékenységek kapcsán érzékelhető öregedő közönségbázis bővítése (Šimic-Pap, 2019). Napjaink fogyasztói -főleg a fiatalabbak -jellemzően értékelik a kreatív, innovatív produkciókat, igénylik az aktív bevonást és a több érzékszervre ható impulzusokat; az előadásokat pedig főképp a funkcionális (minőség, ár, helyszín) és az emocionális (a produkcióhoz kötődő érzelmek) dimenziók mentén értékelik (Ercsey, 2014).…”
Section: Innovatív Repertoár -úJ Közönségréteg Megszólítása éS Bevonásaunclassified
“…Annak érdekében, hogy a jövőben is legyen zeneszerető közönségbázis, nagy figyelmet kell fordítani a fiatalabbak megszólítására és a "célpiac" kibővítésére, azaz új közönségrétegek elérésére. A fogyasztói elégedettség növelése, illetve új fogyasztók megszólítása kapcsán alapvető fontosságú az előadások célközönségének, az egyes fogyasztói szegmensek speciális igényeinek, elvárásai nak, érdeklődési körének megismerése, hiszen így válik lehetővé a kulturális tevékenységek kapcsán érzékelhető öregedő közönségbázis bővítése (Šimic-Pap, 2019). Napjaink fogyasztói -főleg a fiatalabbak -jellemzően értékelik a kreatív, innovatív produkciókat, igénylik az aktív bevonást és a több érzékszervre ható impulzusokat; az előadásokat pedig főképp a funkcionális (minőség, ár, helyszín) és az emocionális (a produkcióhoz kötődő érzelmek) dimenziók mentén értékelik (Ercsey, 2014).…”
Section: Innovatív Repertoár -úJ Közönségréteg Megszólítása éS Bevonásaunclassified
“…A recent study (Leko Šimić & Pap, 2019) on theatre visitors' satisfaction has also identified differences between the two age groups and visiting frequency. The occasional visitors' segment was the most critical, and the discrepancies between the expectations and experiences were highest, in general.…”
Section: Cluster Analysis -Adult Audiencementioning
confidence: 99%
“…The same situation exists in Croatia, and if this is related to the longterm trend of the decline of classic theatre audiences (Leko Šimić & Pap, 2020), it is clear that a detailed age segments analysis is needed. Moreover, although several newer studies have concentrated on motivational factors (Walmsley, 2011;Obaidalahe & Steils, 2018), engagement (Pap et al, 2017), satisfaction (Leko Šimić & Pap, 2019) and other factors affecting theatre attendance, Hager and Kopczynski Winkler (2012) warned that neither scholars nor managers can afford to underemphasize the value of demographics in predicting performing arts attendance. This paper is the first in Croatia that studies has studied the different classic theatre segments and to provide insight into youth and adult theatre consumers' profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In order to have a music-lover core audience in the future as well, great attention must be paid to reaching out to new segments, especially younger people, and expanding the target market. In this process, it is essential to get to know the target audience of the performances and the special needs, expectations and interests of each customer segment, as this makes it possible to expand the aging audience (Šimic & Pap, 2019). Today's consumers, especially the younger ones, typically appreciate creative, innovative productions, demand active involvement and multi-sensory experiences, and evaluate performances mainly along the functional (quality, price, location) and emotional (productionrelated emotions) dimensions (Ercsey 2014).…”
Section: Innovative Repertoire -Addressing and Involving New Audiencesmentioning
confidence: 99%